Efficiency of Electromyographic Examination in Dental Patients with Signs of Bruxism to Determine the Functional State of the Muscles of the Maxillofacial Region - S. P. Rubnikovich; A. S. Grishchenkov; Y. L. Denisova; E. V. Kuzmenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The bioelectrical activity of the masticatory and temporal muscles at rest and under voluntary ten  sion in patients with clinical signs of bruxism was assessed. An excess of the average amplitude values for the right and left masticatory and temporal muscles under voluntary tension was found in patients with clinical signs of bruxism compared to patients in the control group. The study of the average resting amplitude for the masticatory and temporal muscles in patients with signs of bruxism compared to patients in the control group allowed us to determine an increase in values for both the masticatory and temporal muscles. The obtained data indicate persistent functional disorders of the muscles of the maxillofacial region in patients with clinical signs of bruxism, which is characterized by a pronounced deviation in the values of the average and maximum amplitudes at rest and under voluntary tension, as well as asymmetry of the amplitude-frequency characteristics. Analysis of bioelectr ical activity data of masticatory and temporal muscles at rest and under voluntary tension after a course of comp lex therapy indicates a marked decrease in this indicator and its tendency to similar values in patients of the control group. The revealed asymmetry of bioelectrical activity of temporal muscles after the course of therapy was not determined, but it remained at the same values in the masticatory muscles proper, which is due to the complexi ty of the symptom complex, including bruxism and disorders of the masticatory-speech apparatus and requiring an expansion of the rapeutic methods of etiopathogenetic orientation. The effectiveness of the complex of treatment methods will be higher with the use of pathogenetic therapy.